Does Vitamin B12 Deficiency in Infants Cause Severe Clinical Symptoms Necessitating Intensive Care? - Neslihan Karakurt; Canan Albayrak; Nazik Yener; Davut Albayrak (Galenos Yayinevi, 2019)
Introduction:Cobalamin (Cbl) deficient infants are mostly outpatients. Medical literature is very limited concerning infants with severe Cbl deficiency requiring intensive care. The aim of this study was to describe infants requiring intensive care whose health issues were primarily related to Cbl deficiency.Methods:This is a single-center retrospective observational study performed at the pediatric intensive care unit at a children's hospital. Patients aged 6-24 months with low serum Cbl level coexisting with cytopenia (s) and/or macrocytosis, high levels of iron, ferritin and transferin saturation and whose clinical symptoms necessitating intensive care at diagnosis and resolving after Cbl therapy were included. Infants with chronic diseases and birth asphyxia history were excluded.Results:Seven infants were included in the study. The mean age and Cbl level at presentation was 11±5 months and 50±27 pg/mL, respectively. The presenting complaints were diarrhea, vomiting, difficulty swallowing, seizure, respiratory distress and cyanosis after feeding. Three patients needed mechanical ventilation. Megaloblastic changes were detected in five patients who underwent bone marrow aspiration. Cerebral atrophy was found in six of the patients on cranial imaging. Only one patient developed neurological disability during long-term follow-up.Conclusion:This retrospective study was performed to emphasize the importance of Cbl deficiency in infants requiring intensive care or who had serious deterioration of organ functions. Cbl deficiency in children may lead to life-threatening complications such as respiratory failure or neurological disorders. Prompt diagnosis and immediate treatment may not only be life saving but also improves quality of life in long-term follow-up.